ACTUAL PROBLEMS OF PERSONNEL POLICY AT THE ENTERPRISES OF PASSENGER MOTOR TRANSPORT - Y. Proshina (Вестник университета, 2016)
In the article the urgency of formation and implementation of personnel policies at the sector enterprises. The role of the labor potential in securing and improving the competitiveness of the passenger motor transportation enterprises. Major issues of personnel policy of the passenger transport company by key categories of staff. The focus is on driving employment potential as the dominant factor of influence on the personnel policy of the public transport company. The generated model of a real personnel policy passenger transport company to date and it identifies the main "bottlenecks". In conclusion, the evaluation of the status of the personnel policy in the General structure of various areas of functioning of the passenger motor transport enterprise.